Drivers of onward HIV transmission risk among adolescent boys growing up with HIV: a longitudinal cohort study - Avy Violari; Xiaoyue Zhang; Rachel Kidman; Janan Janine Dietrich; Stefanie Vermaak; Candice W Ramsammy; Phumla Madi; Given Leshabane (BMJ Public Health, 2025)
Introduction HIV transmission to sexual partners is determined jointly by viraemia and condomless sex, both of which are higher among adolescents living with HIV compared with adults. Moreover, decisions around condom use vary day to day. We are the first study to investigate both the stable and time-varying factors contributing to HIV transmission risk.Methods The cohort study enrolled 251 adolescent boys 15–19 years old who were born with HIV and resided in Soweto, South Africa. Participants had viral load testing concurrently with completing baseline and 12-month follow-up surveys. Over the study year, participants completed repeated mobile surveys to capture time-variant exposures and condom use in the past 24 hours. Associations between baseline factors and high transmission risk (a composite of detectable viral load and any reported non-condom use) were analysed using logistic regression models. Associations between time-variant factors and condomless sex were analysed using generalised linear mixed-effect models.Results Experiencing an additional adverse event in the last year (adjusted OR (aOR) 1.33; 95% CI 1.09, 1.64), intimate partner violence (IPV; aOR 6.07; 95% CI 1.69, 21.80) and depression (aOR 2.96, 95% CI 1.03, 8.57) each increased the adjusted odds of being in the high-risk group for HIV transmission. When we examined time-variant factors, we found that a 10% higher average experience of stress (aOR 1.23; 95% CI 1.04, 1.46) and anger (aOR 1.26; 95% CI 1.04, 1.53) was significantly associated with increased odds of having condomless sex. There was no evidence that day-to-day changes in exposure to potential risk factors influenced condom use decisions.Discussion Global strategies largely focus on reducing HIV infection risk from the perspective of adolescent girls and young women. This study adds to the growing evidence that childhood adversity, IPV victimisation and depression are related to sexual transmission risk, and importantly extends this finding to the expanding population of adolescent boys born with HIV. Tailoring violence and mental health support services to the needs of adolescent boys may have important implications for their well-being and the health of their partners.